J774 macrophage-like cell line cytokine and chemokine patterns are modulated by Francisella tularensis LVS strain infection - Holická-Černá, Monika; Novosad, Jakub; Trojáčková Kudlová, Manuela; Loudová, Martina; Krejsek, Jan; Andrýs, Ctirad (Folia microbiologica, 2010)
Mutual interactions were investigated between intracellular parasitic bacterium Francisella tularensis (F.t.; highly virulent bacterium responsible for tularemia, replicating within the host macrophages) and murine macrophage-like cell line J774. Recombinant murine lymphokine INF-gamma and/or LPS derived from E. coli were determined to stimulate in vitro antimicrobial activity of macrophage-like J774 cell line against the live vaccine strain (LVS) of F.t. through their ability to produce proinflammatory cytokines and chemokines. F.t. infection up-regulated IL-12 p40 production and down-regulated TNF-alpha production by stimulated macrophages; on the other hand, F.t. infection did not affect the production of IL-8, IL-6, MCP-5, and RANTES by stimulated macrophages. This showed that F.t. infection modulates the cytokine synthesis by J774 macrophage cell line.
Keywords: tularemie; financování organizované; chemokiny; Animals; Cell Line; cytokiny; Financing, Organized; Chemokines; Tularemia; zvířata; buněčné linie; Francisella tularensis; Cytokines; Macrophages; Mice; makrofágy; myši